Internal audit function and investment efficiency: Evidence from public companies in Indonesia - Ardianto Ardianto; Nadia Anridho; Agnes Aurora Ngelo; Wulandari Fitri Ekasari; Imran Haider (Cogent Business & Management, 2023)
AbstractThis study examines the relationship between internal audit functions and investment efficiency. We want to test the involvement of internal audit functions in corporate strategic management decisions like investment efficiency. This study employs all non-financial public listed on the Indonesia Stock Exchange from 2016 to 2019, and we obtained 1,360 firm-year observations. We discover that the internal audit function negatively affects corporate investment efficiency. This implies that the internal audit function has a minor role in giving value-added service regarding investment decisions in the context of listed public companies in Indonesia. Our result is robust to the endogeneity test of Heckman Two-Stages regression. Therefore, in the context of corporate strategic decisions like investment efficiency, we document that the internal audit function does not efficiently enhance the efficiency of corporate investment decisions in the setting of Indonesian public companies. We expect this result to improve the insight regarding the internal audit function in Indonesia and encourage the practice of internal audit function in Indonesian publicly listed companies to increase their efficiency in performing their consulting role for giving value-added service to management, especially in terms of investment decisions.